Mitochondrial quality control measures, systemic inflammation, and lower-limb muscle power in older adults: a PROMPT secondary analysis - Helio José Coelho-Junior; Emanuele Marzetti; Casey L. Sexton; Kevin Wu; Robert Mankowski; Stephen D. Anton; Christiaan Leeuwenburgh; Anna Picca (Elsevier, 2024)
Objectives: The study was conducted to explore associations between markers of mitochondrial quality control (MQC) from vastus lateralis muscle biopsies, serum inflammatory markers, and measures of muscle power assessed by two different tools in a sample of older adults. Design: Secondary analysis of data collected in the PeppeR develOpMental ProjecT (PROMPT) at the University of Florida (Gainesville, FL, USA). Methods: Forty-three older adults (n = 20 women) were included in the study. Muscle volume of the calf and thigh was quantified by three-dimensional magnetic resonance imaging. Lower-limb muscle power was estimated using 5-time sit-to-stand (5STS) muscle power equations and isokinetic test. Protein markers of MQC were measured in muscle samples by Western immoblotting (n = 12-23), while type I and II fiber cross-sectional area (CSA) and their proportion were quantified using immunohistochemistry (n = 12). Cytochrome C oxidase enzyme activity was measured spectrophotometrically. Finally, inflammatory markers were quantified in the serum using a multiplex immunoassay (n = 39). Results: Mean age of participants was 78.1 ± 5.5 years, and the average body mass index was 26.2 ± 4.5 kg/m2. Markers of mitochondrial biogenesis (i.e., PGC-1α), mitochondrial import proteins (i.e., cHsp70 and mtHsp70), and type I fiber CSA were significantly associated with muscle power estimated via both 5STS muscle power equations and isokinetic test (p < 0.05). Specific associations were also found according to the muscle power assessment method. 5STS muscle power measures were negatively correlated with ClvCasp3, P-AMPK, T-AMPK, P-p38, GM-CSF, INF-γ, IL1b, IL6, IL8, and TNF-α, whereas positive associations were found with BAX (p < 0.05). In contrast, isokinetic measures were significantly and positively correlated with RIP140, Hsp60, and type II muscle fiber CSA (p < 0.05). Conclusions: Markers of mitochondrial biogenesis (PGC-1α), mitochondrial import proteins (cHsp70 and mtHsp70), and type I muscle fiber CSA were significantly linked to lower-limb muscle power in older adults. These results suggest that muscle power is influenced by mitochondrial signaling. We also found that the relationship between mitochondrial mediators, inflammatory markers, and muscle power varied according to the assessment tool used.